Visual Representations – Handbook of the Anthropocene in Latin America VI - Gerardo Cham; Juan Arturo Camacho Becerra; Olaf Kaltmeier; Elissa Rashkin (BiUP, 2026)
Throughout the history of the Americas, sentiments toward the environment have been problematized and aestheticized through visual representations in various formats. In this volume of the Handbook »The Anthropocene as Multiple Crisis«, sixty entries examine the crises of mining, energy, land use, biodiversity, water, and climate change in the major macro-regions of Latin America from the colonial period to the contemporary era of the Anthropocene, featuring iconic images from this context.